Power and discrete rate adaptation in BER constrained wireless powered communication networks. Issue 18 (15th October 2018) - Lei, Ming; Zhang, Xingjun; Yu, Bocheng; Dong, Xiaoshe
Abstract : Optimal system throughput is a crucial design issue in wireless powered communication networks. Unlike related literature, this study considers the problem of maximising throughput (MTP) for a practical scenario, in which each user node (UN) selects its own rate from a discrete rate set and controls its transmission power according to its own channel state. The MTP with a bit‐error‐rate constraint is investigated based on two general uplink access methods. The formulation size is exponentially large with respect to the problem input. A novel greedy algorithm based on the column generation method (GA‐CGM) is proposed to solve the problem efficiently. The GA‐CGM decomposes the problem into a master problem and a subproblem. The master problem is solved by the simplex method. The subproblem is solved by a greedy algorithm due to its non‐linearity programming model. The max–min throughput problem (MMTP) is also considered, because of the 'doubly near‐far' phenomenon which leads to the unfair throughput among different UNs. Experimental results demonstrate that the proposed solutions are close to the optimal solutions for MTP and MMTP problems. They also show increasing the transmission power of a base station or decreasing the path‐loss exponent improves the throughput performance.